“Blautr erum bergis fótar borr”: Disabled Masculinity and Irregular Phalli in the Íslendingasögur - Morrow, Meg S. (Scandinavian-Canadian Studies / Études scandinaves au Canada, 2026)
Numerous medieval Icelandic sagas discuss men who have irregular phalli. While previous studies have attempted to understand the relationship between medieval Icelandic men and their irregular penises through a psychoanalytic lens, this article instead focuses on the intersection of disability theory and masculinity theory (known as “disabled masculinity”) to examine the cultural and social implications of having an irregular phallus in the medieval Icelandic world, which will be labeled as a “sexual disability.” As this study will reveal, these sexual disabilities were perhaps the most culturally disabling for men in the medieval Icelandic world because of the gender-specific significance of the penis and its impact on their perceived masculine performance.